Senescence: Pathogenic Driver in Chronic Obstructive Pulmonary Disease - Melissa Rivas; Gayatri Gupta; Louis Costanzo; Huma Ahmed; Anne E. Wyman; Patrick Geraghty (Medicina, 2022)
Chronic obstructive pulmonary disease (COPD) is recognized as a disease of accelerated lung aging. Over the past two decades, mounting evidence suggests an accumulation of senescent cells within the lungs of patients with COPD that contributes to dysregulated tissue repair and the secretion of multiple inflammatory proteins, termed the senescence-associated secretory phenotype (SASP). Cellular senescence in COPD is linked to telomere dysfunction, DNA damage, and oxidative stress. This review gives an overview of the mechanistic contributions and pathologic consequences of cellular senescence in COPD and discusses potential therapeutic approaches targeting senescence-associated signaling in COPD.